Um modelo euleriano de dispersão de contaminantes aplicado em diferentes condições de estabilidade atmosférica - Brauer, Cristian Ricardo Nin (2004)
This work describes a model for contaminant dispersion under different atmospheric stability conditions. It can be used to simulate the concentration of contaminants released from sources located at different heights in the PBL. Eddy diffusivities are derived for a convective and mechanical turbulence. These eddy diffusivities are introduced into an Eulerian air pollution model to simulate observed concentration data from the Copenhagen, Prairie Grass and Kinkaid experiments. The simulated concentrations are compared to the observed data to validate the above-mentioned model. A set of statistical indices is applied to the data and they are compared with data from a gaussian model and with data from CALPUFF model. These comparisons lead to the conclusion that the Eulerian air pollution model yields the best results for the Copenhagen and Prairie Grass experiments, because the physical parameters that describe the turbulent field varies with height (the height of the PBL is discretized in N subintervals). Furthermore, the model can also be used in inhomogeneous turbulence conditions, whereas the gaussian models can be used only in homogeneous and stationary turbulence conditions.